Math, asked by bishnoiladla, 1 year ago

(4/5+2/1)(3/1-2/3) solve ​

Answers

Answered by Anonymous
1

Answer:

 = ( \frac{4}{5}  +  \frac{2}{1} )( \frac{3}{1}  -  \frac{2}{3} ) \\  \\  =(  \frac{4 + 10}{5} )( \frac{9 - 2}{3} ) \\  \\  =  \frac{14}{5}  \times  \frac{7}{3}  \\  \\  =  \frac{98}{15}

Step-by-step explanation:

Hope it helps you.........

please mark it as brainliest...........

Answered by uday379
1

Step-by-step explanation:

98/15 is the answer of your question

Similar questions